CARDIOMETABOLIC PROFILE OF OLDER PERSONS IN THE 8TH PHILIPPINE NATIONAL NUTRITION AND HEALTH SURVEY - Lusica, Patricia Marie M; Jimeno, Cecilia A (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION The prevalence of metabolic syndrome (MetS) among Filipino adults was found to be 12 to 15% in 2003. While diet has been one of the identified modifiable risk factors targeted to prevent cardiovascular disease or its complications, the association of each macronutrient component with MetS remains unclear. In the absence of Philippine data on macronutrient intake and cardiometabolic diseases, the primary objective of this study was to determine the association of food intake with cardiometabolic diseases among Filipino adults. METHODOLOGY This study utilized a cross-sectional analytic design. Data from the results of the 8th National Nutrition Survey (NNS) in 2013 to 2015 by the Food and Nutrition Research Institute was used. Filipino adults from different regions of the Philippines who consented to participate in the interview, anthropometrics, blood collection for clinical data and other measurements were included in this study. RESULTS There were 8,056 adults included in the NNS 2013. The prevalence of metabolic syndrome was 33%. Median total calorie intake per day was 1,524.1 kcal (range 148.3 to 7349.5). Median total carbohydrates, protein and fat intake in one day were 273.3 g (range 33.8 to 1309.2), 49.4 g (range 2.8 to 273.3) and 19.8 g (range: 0.2 to 334.9), respectively. Multivariate analysis showed that the following were associated with an increased risk for MetS: increased total protein intake [OR 1.391 (1.150-1.684)], increased daily consumption of meat and poultry [OR 1.397 (1.163-1.677)], and low vegetable intake [OR 1.3 (1.080-1.565)]. CONCLUSION Increased age, higher socioeconomic status, female sex, increased total protein intake and daily consumption of meat and poultry and low vegetable intake are associated with an increased risk for MetS